Perspective for life insurnace companies in indian market - Kirpekar, Rohan Ravindra (Journal of Management and Science, 2013)
This research aims to examine the Perspective of Life Insurance Companies in Indian Market with Current Scenario. As well as need to create new Consumer & maintain the existing Consumer‘s loyalty. A sample of 100 taken the sample size of 100 individuals was selected on the basis of convenient sampling technique. Research Finding indicates Essential Future strategies require applying for Insurance Companies & some new policies.